1998
DOI: 10.1210/en.139.10.4037
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Regulation of Intracellular Signaling and Neurosecretion in Gonadotropin-Releasing Hormone Neurons

Abstract: Agonist activation of cholinergic receptors expressed in perifused hypothalamic and immortalized GnRH-producing (GT1-7) cells induced prominent peaks in GnRH release, each followed by a rapid decrease, a transient plateau, and a decline to below basal levels. The complex profile of GnRH release suggested that acetylcholine (ACh) acts through different cholinergic receptor subtypes to exert stimulatory and inhibitory effects on GnRH release. Whereas activation of nicotinic receptors caused a transient increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
(29 reference statements)
1
31
0
Order By: Relevance
“…Compared with static cultures (42), this perifusion model presents the advantage of minimizing potential autocrine or paracrine effects occurring in vitro, because the effluent is continuously washed out of the chamber. We were also able to measure neurotransmitter secretion from a much lower number of neurons than previously reported using hypothalamic neurons adsorbed onto Biogel beads (43). This difference suggests that preservation of the neuronal network upon transfer into the perifusion chambers may result in increased cellular viability and possibly better preservation of normal cellular functions.…”
Section: Discussionmentioning
confidence: 78%
“…Compared with static cultures (42), this perifusion model presents the advantage of minimizing potential autocrine or paracrine effects occurring in vitro, because the effluent is continuously washed out of the chamber. We were also able to measure neurotransmitter secretion from a much lower number of neurons than previously reported using hypothalamic neurons adsorbed onto Biogel beads (43). This difference suggests that preservation of the neuronal network upon transfer into the perifusion chambers may result in increased cellular viability and possibly better preservation of normal cellular functions.…”
Section: Discussionmentioning
confidence: 78%
“…1, B and C). GnRH receptors are primarily coupled to G q/11 proteins, but some of the physiological actions of GnRH are known to occur through activation of G s or G i proteins (5,33). In GT1-7 neurons, nanomolar GnRH concentrations cause marked elevation of inositol phosphate production through G q -mediated activation of phospholipase C and also stimulate cAMP production.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to regulating pituitary gonadotropin release, GnRH has extrapituitary actions in neural and nonneural tissues and in several types of tumor cells (1). Immortalized GnRH-producing neurons (GT1-7 neurons) express several G protein-coupled receptors (GPCRs), including those for GnRH and luteinizing hormone/ human chorionic gonadotropin (2,3), as well as ␣-and ␤-adrenergic (4), muscarinic (5), and serotonergic receptors (6). These cells retain many of the characteristics of the native GnRH neurons, including the ability to maintain pulsatile GnRH release (1,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, oscillations in cAMP levels, regulated by cyclic nucleotide phosphodiesterases as well as activation of PKA have been implicated in a negative feedback mechanism involved in timing the pulsatile release of GnRH from GT1-7 cells (47,65). It has been suggested that acetylcholine modulates GnRH release from GT1-7 cells via increases in PLC and inhibition of cAMP through both muscarinic (M) 1 and M 2 receptors that are coupled to G q/11 and G i proteins respectively (66). Stimulation of PKC activity (61,62,67) and elevation of intracellular cGMP levels (68) have also been shown to enhance GnRH secretion from GT1-7 cells.…”
Section: Discussionmentioning
confidence: 99%